Use of Problem-Based Digital Comics in the Era of Disruption as an Increasing Effort Critical Thinking Skills and Learning Achievement - Eva Nurchurifiani; Hajjah Zulianti (CV. Tripe Konsultan, 2021)
Learning in the era of disruption is directed at using technology optimally, and learning is directed to have critical thinking skills. Directed learning has critical thinking skills that make it difficult for students to understand the material, which causes student learning achievement to be not optimal. The teaching carried out has not been carried out innovatively due to the teacher's limitations, technological capabilities, and media. So far, learning has only conventionally. This makes students' interest in learning less and less because it is difficult to understand the material. This study aimed to determine the use of problem-based digital comics on learning achievement and critical thinking skills. The method used is a literature review. The study results show that problem-based digital comics in the era of disruption can develop critical thinking skills and improve learning achievement.